Development of Whey Choco Ball and Its Characterization (Journal of Science and Technology Research, 2026)
Dumping whey into sewage caused a substantial loss of nutrients, highlighting the failure to effectively utilize this valuable resource. The goal of this work was to use response surface modeling to determine the ideal conditions for alcalase-acylation of Whey Protein Concentrate (WPC) in order to generate protein hydrolysates with antioxidant and amino acid properties. In this work, we developed a whey-based readyto- eat product called Whey Choco Ball (WCB) using the extracted WPC. Nutritional content, sensory assessment, and textural evaluation in addition to its microbiological examination and shelf life of newly developed product were assessed. The WCB formulation was high in protein, low in fat, and high in mineral content. Additionally, compared to locally available Brands 1, 2, and 3, WCB appears to have less fat (~10.0%), more protein (~10%), less total sugar (~5%) suggesting the product as one of the best sources of protein, and minerals. The product received a score of 9 for color ("liked extremely"), while taste, flavor, mouth feel, texture, and overall acceptance each scored 8 ("liked very much"), reflecting a generally positive sensory evaluation. From a microbiological viewpoint, WCB was considered appropriate up to 15 days. The sensory evaluation panel marked the product at a satisfactory level. Microbial analysis also showed the acceptable validity of that product. The texture analyzer showed different textural parameters that will be helpful for the consumer’s approval. The analysis indicates that WCB can be recognized as a protein-rich food item due to its effective utilization of whey. The incorporation of WPC in WCB contributes significantly to its protein content, showcasing the product's ability to harness the nutritional benefits of this valuable by-product.J. of Sci. and Tech. Res. 6(2): 151-162, 2025